2016
DOI: 10.1016/j.hal.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Role of toxic and bioactive secondary metabolites in colonization and bloom formation by filamentous cyanobacteria Planktothrix

Abstract: SummaryBloom-forming cyanobacteria Planktothrix agardhii and P. rubescens are regularly involved in the occurrence of cyanotoxin in lakes and reservoirs. Besides microcystins (MCs), which inhibit eukaryotic protein phosphatase 1 and 2A, several families of bioactive peptides are produced, thereby resulting in impressive secondary metabolite structural diversity. This review will focus on the current knowledge of the phylogeny, morphology, and ecophysiological adaptations of Planktothrix as well as the toxins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
123
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 176 publications
(227 reference statements)
7
123
0
1
Order By: Relevance
“…However, in this study the application of the linear regression to the mcyB + cells and MC reduced the percentage of MC variation explained, from >80% to ~50%, i.e., a value very close to what was observed by Briand et al (2008) in a population of P. agardhii and consistent with what we previously described in Lake Vico (Manganelli et al, 2016). There are several possible explanations for this outcome, as summarized in Kurmayer et al (2016), such as other coexisting non identified toxic species, problems in the amplification of mcy genes or mutation inactivating mcy genes. Or it could be also hypothesized that other factors, in addition to the genetic make up, influence the relationship between density and toxicity, and the relation between the whole population and MC, representing the environmental cell quota (ECQ, sensu Salmaso et al, 2014), includes those factors.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, in this study the application of the linear regression to the mcyB + cells and MC reduced the percentage of MC variation explained, from >80% to ~50%, i.e., a value very close to what was observed by Briand et al (2008) in a population of P. agardhii and consistent with what we previously described in Lake Vico (Manganelli et al, 2016). There are several possible explanations for this outcome, as summarized in Kurmayer et al (2016), such as other coexisting non identified toxic species, problems in the amplification of mcy genes or mutation inactivating mcy genes. Or it could be also hypothesized that other factors, in addition to the genetic make up, influence the relationship between density and toxicity, and the relation between the whole population and MC, representing the environmental cell quota (ECQ, sensu Salmaso et al, 2014), includes those factors.…”
Section: Discussionsupporting
confidence: 90%
“…The strong relationship between CB and MC in P. rubescens implies a high stability of population genetic structure over time (Salmaso et al, 2014;Kurmayer et al, 2016), which is indeed what we found in the Flumendosa reservoir. But this is not always the case: in Lake Vico (Central Italy), where P. rubescens was dominant, the fraction of the mcyB + cells was highly variable over time, especially during the blooms.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Unlike T. bourrellyi, P. rubescens has these structures and, therefore, has an important competitive advantage. P. rubescens is able to move along the water column and consequently acquire the most favorable position [4,[63][64][65][66][67]. The physiological features and environmental factors that allow the co-presence of these two Cyanobacteria have not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of gas vesicles in this species could allow the overcoming of the tendency of Cyanobacteria to sink out of the euphotic zone, providing P. rubescens with a competitive advantage. Changes in cellular weight due to photosynthesis and respiration processes can be balanced with gas vesicles [65,66,81]. Moreover, the buoyancy ability allows each species to optimize light absorption and obtain the most favorable positioning in the water column.…”
Section: Discussionmentioning
confidence: 99%